Auditoría de gestión a la unidad de compras públicas de la universidad técnica de Cotopaxi, cantón Latacunga período del 1 de enero al 31 de diciembre del 2014 - Chuquitarco Chicaiza, Sofía Nataly (2016)
The present research is addressing to the application of management audit that allowed determining how efficient and effective the public hiring process at Technical University of Cotopaxi from January 1st to December 31st, 2014. The work began introducing the description of different definitions of biographies, it was applied research methodologies on descriptive and exploratory research, the no-experimental design to the study unit considered that workers of financial and administrative department that applied methods were inductive, deductive, analytic, synthetic and dialectic. And also techniques as interview, survey, and direct observation through the analysis and interpretation which allowed getting the purpose to do the audit outstanding the following results: lack of unit planning, lack of relevant document post….